PTEN Deletion in Adult Mice Induces Hypoinsulinemia With Concomitant Low Glucose Levels - Crespo-Masip, Maria; Pérez-Gómez, Aurora; Guzmán, Carla; Rayego, Sandra; Doladé, Nuria; García-Carrasco, Alicia; Jover, Ramiro; Valdivielso, José Manuel (Frontiers in Endocrinology, 2022)
The PI3K/AKT pathway, negatively regulated by PTEN, plays a paramount role in glucose metabolism regulation due to its activation by the insulin receptor signaling pathway. We generated a PTEN-KO mouse to evaluate the systemic effect of the overactivation of the PI3K/AKT pathway in insulin signaling and glucose homeostasis. Our results demonstrate that PTEN-KO mice show very low glucose levels in the fasted state, which poorly respond to glucose and pyruvate administration. Insulinemia decreased without alterations in pancreatic islets. Among the possible reasons, we uncover the deregulation of the expression of proximal tubule glucose transporter and consequent glycosuria. Moreover, we evidence an altered activation of hepatic gluconeogenesis-related genes. In addition, the expression of several genes related to β-oxidation showed a delayed or even absent response to fasting, suggesting that the lack of PTEN not only alteres glucose metabolism but also slows down the use of lipids as a metabolic fuel. We conclude that the inducible full PTEN-KO mice could be a good model to study the metabolic interactions between glycidic and lipidic metabolism in hypoinsulinemic hypoglycemia and that PTEN could be an important mediator in the disease and/or a potential drug target.